2011
DOI: 10.1158/1078-0432.ccr-11-0821
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of PF-04929113 (SNX-5422), an Orally Bioavailable Heat Shock Protein 90 Inhibitor, in Patients with Refractory Solid Tumor Malignancies and Lymphomas

Abstract: Purpose To determine the maximum tolerated dose (MTD), toxicities, and pharmacokinetic-pharmacodynamic profile of the heat shock protein 90 (Hsp90) inhibitor PF-04929113 (SNX-5422) in patients with advanced solid tumors and lymphomas. Methods This was a single institution, phase I, dose-escalation study of PF-04929113 dosed twice-weekly. Endpoints included determination of dose-limiting toxicities (DLT), MTD, the safety profile of PF-04929113, pharmacodynamic assessment of PF-04929113 on Hsp70 induction, pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 30 publications
2
72
1
Order By: Relevance
“…Visual disturbances also occurred; these events were typically transient and low grade. Ophthalmologic toxicity may be an inherent property of potent water-soluble HSP90 inhibitors, as these findings have been reported with other agents, including 17-DMAG and AUY922 (8,25,26). Other commonly occurring AT13387 treatmentrelated AEs ($30%) included nausea and injection site events and systemic infusion reactions, all of which were grade 1 or 2 and managed prophylactically or treated symptomatically.…”
Section: Discussionmentioning
confidence: 76%
“…Visual disturbances also occurred; these events were typically transient and low grade. Ophthalmologic toxicity may be an inherent property of potent water-soluble HSP90 inhibitors, as these findings have been reported with other agents, including 17-DMAG and AUY922 (8,25,26). Other commonly occurring AT13387 treatmentrelated AEs ($30%) included nausea and injection site events and systemic infusion reactions, all of which were grade 1 or 2 and managed prophylactically or treated symptomatically.…”
Section: Discussionmentioning
confidence: 76%
“…Visual AEs were reported, which were most frequent at the higher (40-70 mg/m 2 ) dose levels, although typically grade 1 to 2, and were reversible following interruption or discontinuation of study treatment. Visual disturbances have been reported with other geldanamycin and non-geldanamycin HSP90 inhibitors (32)(33)(34). These effects may be attributable to HSP90 inhibitor-induced photoreceptor degeneration and possibly related to tissue distribution of water-soluble agents facilitating a high retina/plasma concentration ratio, as well as the retinal elimination profile (35).…”
Section: Discussionmentioning
confidence: 99%
“…TAS-116 addresses the issues that have hampered the clinical development of HSP90 inhibitors because it shows a favorable tissue distribution profile. One of the most notable HSP90-related adverse events universally observed but to differing degrees in the clinic is visual disturbance (18)(19)(20)(21)(45)(46)(47)(48). The observed symptoms include night blindness, photopsia, blurred vision, and visual impairment, which are likely associated with retinal dysfunction (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurological toxicities such as syncope and dizziness were seen in a phase I trial of the purine analogue BIIB021 (17), although there is no evidence to support this to be target or purine-scaffold related. In clinical trials of other HSP90 inhibitors, the most commonly observed HSP90-related adverse events have been visual disorders such as night blindness, photopsia, blurred vision, and visual impairment, though the frequency and degree varied among the compounds (18)(19)(20)(21). For example, 43% of patients suffered visual disturbances in a phase I trial of NVP-AUY922 (21).…”
Section: Introductionmentioning
confidence: 99%